Oral treatment with a Brachystemma calycinum D don plant extract reduces disease symptoms and the development of cartilage lesions in experimental dog osteoarthritis: inhibition of protease-activated receptor 2. Issue 6 (21st June 2009) - Boileau, Christelle; Martel-Pelletier, Johanne; Caron, Judith; Paré, Frédéric; Troncy, Eric; Moreau, Maxim; Pelletier, Jean-Pierre
Abstract : Objective: The aims of this study were to evaluate the effect of oral treatment with a whole plant extract of Brachystemma calycinum D don (BCD) on the development of osteoarthritic lesions and symptoms in the experimental dog anterior cruciate ligament (ACL) transection model and to document its mechanism of action. Methods: Osteoarthritis was induced by sectioning the ACL of the right knee in crossbred dogs. There were two experimental groups (n=6–7 dogs/group): placebo and BCD extract (200 mg/kg per day) given orally for 8 weeks. Macroscopic and histopathological evaluation of cartilage lesions and immunohistochemical analysis of cartilage to assess levels of inducible nitric oxide synthase (iNOS), matrix metalloprotease 13 (MMP-13) and protease activated receptor 2 (PAR-2) were done. A gait analysis of dogs was performed. Results: Treatment with BCD reduced the severity (depth) (p=0.04) and histopathological score (p<0.02) of osteoarthritis cartilage lesions. BCD treatment also significantly reduced the osteoarthritis chondrocyte level of key inflammatory and catabolic factors (iNOS, p=0.009 and MMP-13, p=0.003) as well as the level of PAR-2 (p=0.03). Dogs treated with BCD showed a significant improvement in peak vertical force measured at 8 weeks (p<0.05). Conclusions: Treatment with BCD extract exerts a positive effect on the prevention of cartilage lesions induced by joint instability, and improves joint function. This effect was associated with the inhibition of major catabolic and inflammatory mediators. This study is the first to demonstrate that a therapeutic intervention that can inhibit PAR-2 is associated with a disease-modifying osteoarthritis effect.